2022
DOI: 10.3389/fonc.2022.943154
|View full text |Cite
|
Sign up to set email alerts
|

Comparative review of pharmacological therapies in individuals with HER2-positive advanced breast cancer with focus on hormone receptor subgroups

Abstract: Breast cancer is the fifth leading cause of cancer-related deaths worldwide. The randomized controlled trials (RCTs) of targeted therapies in human epidermal receptor 2 (HER2)–positive advanced breast cancer (ABC) have provided an evidence base for regulatory and reimbursement agencies to appraise the use of cancer therapies in clinical practice. However, a subset of these patients harbor additional biomarkers, for example, a positive hormone receptor status that may be more amenable to therapy and improve ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…Interestingly, some previous studies have also shown the exceptional ability of AKBA to modulate AMPK activity in various tissue. Within this context, it has been documented that AKBA protects against rotenone-induced neurotoxicity and breast carcinoma by activating AMPK [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, some previous studies have also shown the exceptional ability of AKBA to modulate AMPK activity in various tissue. Within this context, it has been documented that AKBA protects against rotenone-induced neurotoxicity and breast carcinoma by activating AMPK [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%